Sekolah Aswaja PMII dan Reproduksi Kesadaran Kader: Analisis Teologi atas Materi Sejarah, Prinsip, dan Mabadi Khairu Ummah - Asep Dhoni Syaiful Milah; Eka Faridatun Khasanah; Alya Iswari; Rara Nuramiyati; Mohammad Roqib (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
The Aswaja School is a cadre development forum organized by PMII Rayon Tarbiyah Walisongo with the main objective of internalizing the fundamental values of the organization, including its historical narratives, core principles, and Islamic teachings rooted in the Ahlussunnah wal Jama’ah tradition. This article aims to critically examine how these values are internalized during the cadre formation process, particularly through the delivery of PMII's history, organizational principles, Aswaja values, and Mabadi Khaira Ummah. This study adopts a participatory qualitative approach in which the author was directly involved as both a participant and a researcher. The findings indicate that methods such as lectures, open discussions, and ideological reflections serve as essential tools in shaping the character of PMII cadres. The Aswaja School is not merely a platform for knowledge transfer but also a reflective and ideological space where cadres develop awareness of their identity and organizational responsibilities. The article recommends enhancing participatory approaches and contextual relevance in future cadre training programs of PMII.